2015
DOI: 10.1017/s1092852915000474
|View full text |Cite
|
Sign up to set email alerts
|

Addictive behaviors and personality traits in adolescents

Abstract: Introduction. Behavioral addictions refer to repeated dysfunctional behaviors that do not involve the ingestion of addictive substances. Studies on the association between behavioral addictions and personality traits have noted in individuals with problematic behaviors a high proclivity toward impulsivity and sensation-seeking and a low predisposition to harm avoidance. The majority of these studies have focused on adults, while far fewer have involved adolescents.Methods. The study population was 109 high sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
2
15
2
3
Order By: Relevance
“…This has vital importance from the perspective of investigating and understanding the development of compulsive overworking, especially in relation to EDs, because similarly to EDs, it can be observed and associated with substantial harm already among adolescents (Wróbel, 2020). Therefore, it is possible to investigate EDs and WA/SA co-occurrence in adolescent populations, which previously happened to be a theoretical and empirical hindrance (see Munno, Saroldi, Bechon, Sterpone, & Zullo, 2016) or scales developed for measuring work would have doubtful validity when used in adolescent and student samples (Pallanti, Bernardi, & Quercioli, 2006; see Griffiths et al, 2018 for information on using WA scales in these samples).…”
Section: mentioning
confidence: 99%
“…This has vital importance from the perspective of investigating and understanding the development of compulsive overworking, especially in relation to EDs, because similarly to EDs, it can be observed and associated with substantial harm already among adolescents (Wróbel, 2020). Therefore, it is possible to investigate EDs and WA/SA co-occurrence in adolescent populations, which previously happened to be a theoretical and empirical hindrance (see Munno, Saroldi, Bechon, Sterpone, & Zullo, 2016) or scales developed for measuring work would have doubtful validity when used in adolescent and student samples (Pallanti, Bernardi, & Quercioli, 2006; see Griffiths et al, 2018 for information on using WA scales in these samples).…”
Section: mentioning
confidence: 99%
“…The prevalence of Internet addiction has been found to be higher in boys than in girls (Ha and Hwang, 2014). Boys have higher impulsivity than girls (Munno et al, 2016). Two previous studies found that women have higher BIS activation and higher activation of specific aspects of the BAS (reward responsiveness) than men (Jorm et al, 1998; Nam et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Other shared features of CBB and GD are the early onset of the problematic addictive problems, (Balogh et al, 2013 ; Maraz et al, 2015b ), low education levels (Maraz et al, 2015a ), high exposure to adverse life events (Lee et al, 2012 ), and specific personality traits (Black et al, 2012 ; Di Nicola et al, 2015 ; Munno et al, 2016 ). It is also noteworthy that both conditions are characterized by deceit and alterations in attitudes toward money, personal financial behavior, and materialistic values (Black et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%